Proposta de consolidação estrutural da Igreja de Nossa Senhora do Monte do Recôncavo - Oliveira, M.; Muñoz, R.; Magalhñes, A. (Revista ALCONPAT, 2014)
The Church of Nossa Senhora do Monte, built in Bahia, Brazil, probably in the eighteenth century, is located in São Francisco do Conde, in the Recôncavo. Currently the building is in a deplorable state of degradation, especially in terms of the roof and stability of the walls. This work proposes intervention measures to stabilize the said structural elements while taking into consideration and respecting the existing structural logic. The following results will be presented: detail of the reinforcement of the wood roof structure of the nave; summary of the project for the replacement of existing wood beams by metal ones; and finally the proposal to repair the vault after the presbytery. This paper emphasizes the importance of this stabilization work as a methodology to be adopted in other historic buildings, since it suggests nondestructive interventions, relevant to sites that have assets of significant historical and cultural value.